The Drivers of Muslim interest in Islamic medical tourism destinations in Indonesia - Firdaus, Firdaus; Abdullah, Zailani; Noegroho, Andro Dewantara; Astono, Ari Dwi; Bilal, Bilal (Faculty of Business & Economics, Universitas Islam Indonesia, 2026)
Objective – This study examines how religiosity influences Muslim tourists’ intention to choose Islamic medical tourism destinations (IMTD) in Indonesia by investigating the mediating roles of attitude and motivation of piety.Methodology – A quantitative research design was employed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4.0. Data were collected from 200 Muslim tourists who were aware of the IMTD. Four constructs—religiosity, attitude, behavioral intention, and motivation of piety—were measured, and the proposed direct and indirect relationships were tested using the bootstrapping procedure at a 5% significance level.Findings – The results reveal that religiosity has a significant positive effect on both attitudes and behavioral intentions. Religiosity also enhances the motivation for piety directly and indirectly through behavioral intention. However, attitude is negatively associated with motivation of piety, suggesting the presence of cognitive–spiritual dissonance in tourists’ decision making. Furthermore, behavioral intention serves as a stronger mediating mechanism than attitude in explaining the influence of religiosity on the motivation of piety.Implications – The findings suggest that IMTD managers and policymakers should prioritize strategies that strengthen Muslim tourists’ behavioral intentions by integrating religious values into destination branding, service design, and promotional activities, rather than relying solely on favorable attitudes.Originality – This study extends the Islamic medical tourism literature by demonstrating that religiosity shapes tourists’ motivation for piety through distinct psychological pathways. It further identifies behavioral intention as a more influential mediating mechanism than attitude, offering new insights into Muslim tourists’ destination-choice behavior.